Curing process, mechanical property and thermal stability of acrylic polyurethane/Fe2O3 nanocomposite coatings - Vy, Do Truc; Hung, Dao Phi; Anh, Nguyen Tuan; Lam, Tran Dai; Vuong, Nguyen Thien (Vietnam Journal of Science and Technology, 2024)
The effect of Fe2O3 nanoparticles (NPs) on the curing and properties of acrylic polyol HSU 1168 based coating were investigated. The SEM images showed that Fe2O3 NPs with the content £ 2 wt.% were dispersed regularly in the polymer matrix. The obtained results indicated that Fe2O3 NPs slowed down the curing process of acrylic polyol coating. Without nanoparticles, the neat HSU 1168 based coating has completely cured after 96 hours, whereas in the presence of 2 wt.% Fe2O3 NPs in coating matrix it needed 120 hours for a full curing. In addition, the relative hardness of nanocomposite coating has reduced with increasing the Fe2O3 NPs content. Without nanoparticles, the relative hardness of neat acrylic polyol coating was 0.88, whereas it was 0.75 when 4 wt.% Fe2O3 NPs was added into the coating matrix. Besides, incorporation of Fe2O3 NPs into the acrylic polyol coating also enhanced its abrasion resistance and impact resistance with 2 wt.% Fe2O3 NPs being the best content (i.e. 200 kG.cm of impact resistance and 408.8 L/mil of abrasion resistance). On the other hand, incorporation of Fe2O3 NPs into the coating matrix improved its thermal stability. The starting temperature for degradation of nanocomposite coating (with 2 wt.% Fe2O3 NPs) was 15 oC higher than that of the neat coating (without nanoparticles)